2018
DOI: 10.1016/j.cmet.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

CD38-NAD+Axis Regulates Immunotherapeutic Anti-Tumor T Cell Response

Abstract: SUMMARY Heightened effector function and prolonged persistence, the key attributes of Th1 and Th17 cells, respectively, are key features of potent anti-tumor T cells. Here, we established ex vivo culture conditions to generate hybrid Th1/17 cells, which persisted long-term in vivo while maintaining their effector function. Using transcriptomics and metabolic profiling approaches, we showed that the enhanced anti-tumor property of Th1/17 cells was dependent on the increased NAD+-dependent activity of the histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
237
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(258 citation statements)
references
References 58 publications
9
237
0
1
Order By: Relevance
“…This is important to note, given that recent studies have spoken to the varied functional status of both peripheral blood and BM T cells from multiple myeloma patients (40,41). Moreover, these findings align with work conducted by Chatterjee et al, which showed that inhibition of CD38 increased NAD + -dependent activity of Sirt1 and enhanced the anti-tumor effect of CD8 + T cells (42). Since the majority of our samples were from WB, we investigated this aspect of T-cell biology for markers associated with CD8 + T-cell exhaustion and showed that the median percentage of PD1 + CD8 + T cells trended downward in responders but tended to increase in non-responders (both not significant).…”
Section: Discussionsupporting
confidence: 85%
“…This is important to note, given that recent studies have spoken to the varied functional status of both peripheral blood and BM T cells from multiple myeloma patients (40,41). Moreover, these findings align with work conducted by Chatterjee et al, which showed that inhibition of CD38 increased NAD + -dependent activity of Sirt1 and enhanced the anti-tumor effect of CD8 + T cells (42). Since the majority of our samples were from WB, we investigated this aspect of T-cell biology for markers associated with CD8 + T-cell exhaustion and showed that the median percentage of PD1 + CD8 + T cells trended downward in responders but tended to increase in non-responders (both not significant).…”
Section: Discussionsupporting
confidence: 85%
“…NAD + is central to mitochondrial energy metabolism, and it also serves as a substrate for Sirtuin family members regulated deacetylation reaction and PARP family members mediated ADP-ribosylation 36,37,51-53 . It was previously reported that a NAD + -Sirt1-Foxo1 axis controls the anti-tumor potential of hybrid Th1/17 cells generated from ex vivo cultures 54 . In contrast to this role of NAD + as a substrate for deacetylation and ADP-ribosylation, we here discovered that NAD + can control T cell activation via regulation of energy metabolism.…”
Section: Main Textmentioning
confidence: 99%
“…Previous studies have reported that CD38 regulates immune cell homing, innate immune responses to pathogens, and anti-tumor immunity [76][77][78] . However, Cd38 remains a largely uncharacterized gene in immunology, despite its widespread use in the field as an activation marker.…”
Section: Discussionmentioning
confidence: 99%